2014
DOI: 10.1111/jsap.12303
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility of lymph node cytology samples in dogs and cats

Abstract: Lymph node cytology is a useful diagnostic procedure but educating veterinarians to improve sampling and smearing may increase diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 10 publications
(9 reference statements)
6
50
4
Order By: Relevance
“…In feline samples, the association was not significant, although this may be due to a smaller sample size (Amores-Fuster et al 2015 ). Of the canine samples, 73% were diagnostic, and of the 199 feline lymph nodes aspirates evaluated, 86% were considered diagnostic.…”
Section: Abdominal Lymph Nodesmentioning
confidence: 86%
See 3 more Smart Citations
“…In feline samples, the association was not significant, although this may be due to a smaller sample size (Amores-Fuster et al 2015 ). Of the canine samples, 73% were diagnostic, and of the 199 feline lymph nodes aspirates evaluated, 86% were considered diagnostic.…”
Section: Abdominal Lymph Nodesmentioning
confidence: 86%
“…Of the canine samples, 73% were diagnostic, and of the 199 feline lymph nodes aspirates evaluated, 86% were considered diagnostic. The most common reasons for a non-diagnostic sample included the absence of nucleated cells, cell disruption and a low yield (Amores-Fuster et al 2015 ). It is important to note that the lymph node samples in this study were not specifically from the abdomen, and in our experience, obtaining samples from abdominal lymph nodes is more likely to be non-diagnostic compared with subcutaneous lymph nodes.…”
Section: Abdominal Lymph Nodesmentioning
confidence: 87%
See 2 more Smart Citations
“…However, it has been suggested that in veterinary medicine excisional biopsy of the lymph node and histopathology should only be considered when cytological examination gives an inconclusive result (Messick 2008, Comazzi et al 2014. Cytology is a cheap, easy to perform, safe and reliable method of lymphoma diagnosis with high accuracy compared to histopathological examination (Amores-Fuster et al 2015). In human oncology, cytological examination allows non-Hodgkin lymphoma to be recognized in 80-95% of cases; additionally, subtyping is possible in 67-86% of lymphomas (Das 1999, Alam et al 2010.…”
Section: Application Of Cytology In Canine Lymphomasmentioning
confidence: 99%